The use of intervention mapping to guide the development of a school-based intervention to improve emergency medical services activation for stroke - Volevach, Ekaterina; Schneider, Francine; Maršálková, Hana; Mikulik, Robert (BMC public health, 2024)
BACKGROUND: If carried out correctly and without delay, activation of emergency services by stroke bystanders could improve mortality and disability from stroke. This paper describes the development of a school-based intervention using the Intervention Mapping approach. It aims to improve the appropriate activation of emergency medical services for suspected stroke by 12-15-year-old children. METHODS: The development of the intervention was guided by Intervention Mapping approach. The logic model of the problem was created through analysis of the existing literature and semi-structured interviews with stakeholders. Based on these findings, performance objectives and their determinants were determined and matched to create a model for changing emergency medical services activation behavior. Behavior change methods and their practical applications were then determined. Based on them, intervention messages and materials were designed, the intervention was drafted, pretested, and finalized. RESULTS: It was found that the main performance objectives for the activation of emergency medical services were (1) recognizing symptoms, (2) communicating with the victim, and (3) calling an ambulance immediately. Their main determinants were knowledge, social influence, risk perception, self-efficacy, outcome expectations, and skills. Determinants were then matched with performance objectives to create the matrices of requested behavior changes. The following change methods were chosen: modeling, elaboration, belief selection, providing cues, scenario-based risk information, and cultural similarity. Methods were translated into practical applications in the form of a short educational film. The production company created, pretested, and finalized the film. As a result, a 5-minute entertainment-education video was created modeling an acute stroke with a child as the main bystander. CONCLUSION: The Intervention Mapping approach guided the development of a school-based program to improve Emergency medical services activation in stroke by 12-15 year old children. Our process and approach can serve as a model for researchers and health promotion professionals aiming to improve help-seeking behavior for stroke to improve stroke help-seeking behavior as well as other acute diseases.
Keywords: urgentní zdravotnické služby; Emergency Medical Services; Stroke; mladiství; školy; mužské pohlaví; Entertainment-education; cévní mozková příhoda; dítě; Child; Schools; Intervention mapping; ženské pohlaví; Humans; školní zdravotnické služby; Program Development; School Health Services; School-based; Emergency medical services activation; Female; Educational intervention; Adolescent; rozvoj plánování; lidé; Male